Comparison of Efficacies of Cysteine Protease Inhibitors against Five Strains of Plasmodium falciparum - Singh, Ajay (American Society for Microbiology, 2001)
Falcipain-2, a cysteine protease and essential hemoglobinase of Plasmodium falciparum, is a potential antimalarial drug target. We compared the falcipain-2 sequences and sensitivities to cysteine protease inhibitors of five parasite strains that differ markedly in sensitivity to established antimalarial drugs. The sequence of falcipain-2 was highly conserved, and the sensitivities of all of the strains to falcipain-2 inhibitors were very similar. Thus, cross-resistance between cysteine protease inhibitors and other antimalarial agents is not expected in parasites that are now circulating and falcipain-2 remains a promising chemotherapeutic target.